Work on mathematical problem solving and its effect on the beliefs of high school students - Vesga-Bravo, Grace Judith; Escobar-Sánchez, Rubén Esteban (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper shows some contributions based on the study of the beliefs that students of basic education have about mathematics and the way in which they can be transformed. Basically, the research was aimed at determining whether a pedagogical proposal based on the theoretical framework of problem solving had an impact on the beliefs of a specific group among the different seventh grade groups. The study was developed under a quantitative approach and the instrument designed and validated by Vizcaíno, Manzano and Casas (2015) was used. This instrument allowed to know the beliefs of the students before and after the intervention, associated to four factors that describe them as naïve or sophisticated. Correlations between final beliefs and participants' gender and academic performance were also analyzed. As part of the results it was determined that after working in problem solving, beliefs related to the speed of learning improved, students were more aware of the importance of making an effort and not giving up if they cannot solve a problem immediately.